Assessing the radiopacity of new root end filling materials using digital radiography technique (Mustansiria Dental Journal, 2019)
Background: Radiographic discrimination of root end filling materials fromsurrounding tooth structure is clinically relevant for assessing the quality ofretrograde treatment. The present study aimed at evaluating the radiopacity ofBiodentine™ and Pro Root MTA as root end filling materials using a digitalradiography technique.Materials and Methods: Specimens of BiodentineTM and Pro Root MTA testmaterials with 1mm thick and 10 mm internal diameter were prepared for digitalradiographic analysis using an aluminum washer. The radiopacity of theBiodentine™ and Pro Root MTA was assessed using dental radiographyequipment in combination with a phosphor plate digital system and a grey scalevalue aluminum step wedge with thicknesses varying from 1 mm to 10 mm insteps of 1 mm each. The degree of radiopacity of the test materials wereradiographed and compared together with the aluminum step wedge on acomputer screen using image J software. Radiopacity was expressed in mm ofequivalent aluminum step wedge. The radiopacity values of Biodentine™ and ProRoot MTA were statistically analyzed using the one way analysis of variance(ANOVA) and post-hoc test (Bonferroni test), the level of significance was set at0.05 (P